Membros: v. 10, n. 1 (2012) - ., .. (RENOTE, 2012)
Alexandra Lorandi Macedo - UFRGS Alessandra Pereira Rodrigues - Instituto Federal Sul Riograndense - Pelotas Alexandre Ribeiro - UCS Ana Carolina B de Marchi - UPF Carla Beatris Valentini - Universidade de Caxias do Sul Carlos Tadeu Queiroz de Morais - PGIE - UFRGS Cleuza Maria Maximino Carvalho Alonso - UFSM Elisa Boff - UCS Eliseo Reategui - FACED/PGIE - UFRGS Evandro Alves - CINTED/UFRGS Gilse Antoninha Morgental Falkembach - UFSM/CINTED Janete Sander Costa - ULBRA Joice Otsuka - UFSCAR José Valdeni Lima - PGIE/UFRGS Liliana Passerino - CINTED/FACED/PGIE - UFRGS Louise Jeanty de Seixas - Faculdade de Farmácia/UFRGS Magda Bercht - Instituto de Informática/PGIE - UFRGS Marcelo Augusto Rauh Schmitt - Instituto Federal do Rio Grande do Sul Marcelo Foohs - Faculdade de Educação / UFRGS Marcia Cristina Moraes - PUCRS Marcia Rodrigues Notare - UNISINOS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Marina Nakayama - UFSC Marlise Geller - ULBRA Michelle Denise Leonhardt - Departamento de Informática Aplicada/UFRGS Patrícia Alejandra Behar - FACED/PGIE - UFRGS Querte Mehlecke - FACCAT/RS Renato Dutra - Universidade Anhembi Morumbi Ricardo Azambuja Silveira - INF/UFSC Roberto dos Santos Rabello - Universidade de Passo Fundo Roseclea Medina - UFSM Silvia Ferreto da Silva Moresco - NUTED/FACED/UFRGS Silvia Meirelles Leite - UFPEL Valéria Costa - PPGIE Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - PGIE/UFRGS